Combining clinical features and MEST-C score in IgA nephropathy may be a better determinant of kidney survival - Yeter Hasan Haci; Gonul Ipek; Guz Gizem; Helvaci Ozant; Korucu Berfu; Akcay Omer Faruk; Derici Ulver; Arinsoy Turgay (Sciendo, 2020)
Introduction. IgA nephropathy (IgAN) is a heterogeneous disease with highly variable clinical and histopathological features. We investigated the effects of Oxford classification and clinical features on renal survival in patients with IgAN.